A highly selective near infrared fluorescent probe for carboxylesterase 2 and its biological applications. Issue 10 (25th February 2021) - Zhang, Xin-Yue; Liu, Tian-Tian; Liang, Jia-Hao; Tian, Xiang-Ge; Zhang, Bao-Jing; Huang, Hui-Lian; Ma, Xiao-Chi; Feng, Lei; Sun, Cheng-Peng
Abstract : Carboxylesterase 2 (CES 2) is a key enzyme in the activation of the prodrug irinotecan (CPT-11) in the treatment against colorectal cancer and also has some relationship with the side effect of CPT-11 in clinical applications. Abstract : Carboxylesterase 2 (CES 2) is a key enzyme in the activation of the prodrug irinotecan (CPT-11) in the treatment against colorectal cancer and also has some relationship with the side effect of CPT-11 in clinical applications. Herein, a near infrared (NIR) fluorescent probe (DSAB ) has been designed for CES 2 which possesses the advantages of prominent selectivity and high sensitivity, and DSAB has been successfully applied for the imaging of endogenous CES 2 in living cells. Moreover, a high-throughput screening method for CES 2 inhibitors has been established using DSAB and discovered four novel CES 2 inhibitors from various herbal medicines. These results fully demonstrated that DSAB is a promising molecular tool for the investigation of the biological functions of CES 2 in living systems and the discovery of novel CES 2 inhibitors for the treatment of CES 2 related physiological diseases.